KAJIAN ETNOBOTANI MASYARAKAT SUKU DAMPELAS DI DESA TALAGA KECAMATAN DAMPELAS KABUPATEN DONGGALA, SULAWESI TENGAH - Satria Dhika Saputra; Wahyu Harso; Ramadanil Ramadanil (Biology Department, Mathematics and natural science, Tadulako University, 2019)
This research entitled “Ethnobotany Study of Dampelas Tribe Community in Talaga Village, Dampelas District of Donggala Regency, Central Sulawesi” and had been conducted from June to August 2016. This research aimed to obtain information about the type of plants and their utilization by Dampelas tribe community. Since the purpose of this research was to find out the type of plants and their utilization, this research employed a descriptive design that used quantitative approach with Equation Index of Cultural Significance (ICS). The equation used in this research was aimed at analysing the cultural importance of a plant. Based on the results obtained from the field, Dampelas tribe community in Talaga Villaga had been utilizing 82 species of plants for their daily life. The researcher dicovered that plants that have the highest ICS value were “Pae” (Oryza sativa L.) and “Aluku” (Cocos nucifera L.). Pae was used as a ceremony material, animal feed and cosmetics, while Aluku or coconut tree was used as handicrafts, building materials and materials for cultural ceremony. Both plants have the highest ICS value which is 104. It was also dicovered that plants that have the lowest ICS score, which was 6, were “Gamir” (Uncaria gambir Hunter Roxb) and “Jarak” (Jatropha Curcas L). Both plants were used as materials for cultural ceremony.